Understanding society: an interview with Daniel Little. Issue 2 (15th March 2023) - Little, Daniel; Morgan, Jamie
ABSTRACT: In this interview, Daniel Little provides an overview of his life and work in academia. Among other things, he discusses an actor-centred approach to theory of social ontology. For Little, this approach complements the assumptions of critical realism, in that it accords full ontological importance to social structures, causal mechanisms, and enduring and influential normative systems. The approach casts doubt, however, on the idea of 'strong emergence' of social structures, the idea that social structures have properties and causal powers that cannot, in principle be explained by their constituents (social actors) and their relationships. Little's approach to social ontology endorses instead the idea of relative explanatory autonomy. During the interview, many points of convergence become evident between this actor-centred approach to social ontology and the fundamental insights of critical realism. According to Little, analysis of social ontology also turns out to be especially relevant to philosophy of history.